2005
DOI: 10.1177/0021998305052036
|View full text |Cite
|
Sign up to set email alerts
|

Defective Repairs of Laminated Solid Composites

Abstract: This paper presents an experimental evaluation of the defective patch repairs of solid laminated composites. The study uses both destructive and nondestructive tests on full-scale repaired panels to evaluate the repair performance under static tension loading conditions. While most reported studies use small coupon specimens, this paper presents test results of full-scale panels that allow strain field monitoring around the patch. The experimental results presented in this paper are the baseline for more advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Although the most efficient solution is to bond overlaminating plies on both the laminate faces [13,14,76], a more practical solution consists on their application only on the outer face of the repair (upper surface in Fig. 2(a)) [38,77]. This choice can also be imposed by accessibility difficulties to the inner face of the composite structure, or be rendered unfeasible for sandwich laminates with composite faces [78].…”
Section: Strength Analysis For the Scarf Repairs With Over-laminatingmentioning
confidence: 99%
“…Although the most efficient solution is to bond overlaminating plies on both the laminate faces [13,14,76], a more practical solution consists on their application only on the outer face of the repair (upper surface in Fig. 2(a)) [38,77]. This choice can also be imposed by accessibility difficulties to the inner face of the composite structure, or be rendered unfeasible for sandwich laminates with composite faces [78].…”
Section: Strength Analysis For the Scarf Repairs With Over-laminatingmentioning
confidence: 99%
“…The most efficient solution is to bond these reinforcements on both the structure faces [31][32][33]. However, a more practical solution consists on their application only on the outer face of the repair [20,34]. This repair scenario can also be imposed by accessibility difficulties to the inner face of the structure, or be rendered unfeasible for sandwich structures [35].…”
Section: Introductionmentioning
confidence: 99%
“…In Structural Repair Manual published by main aircraft manufactures, two kinds of permanent bonded repair methodologies, prepreg repair and wet layup repair, are analyzed for damage tolerance capability . In recent years, considerable studies have been conducted on bonded scarf repair method of laminated structures and sandwich structures . It is shown that scarf repair method is effective to restore the load carrying capabilities.…”
Section: Introductionmentioning
confidence: 99%